Brain on FIRES: Super Refractory Seizure in a 7 year Old Boy - TAVASOLI, Alireza; GHARIB, Behdad; ALIZADEH, Houman; FARSHADMOGHADDAM, Hossein; MEMARIAN, Sara; ASHRAF, Mahmoodreza; sHARIFZADE, Meisam (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Tavasoli AR, Gharib B, Alizadeh H, Farshadmoghaddam H, Memarian S, Ashrafi MR, Sharifzade M. Brain on FIRES: Super refractory seizure in a 7 year old boy. Iran J Child Neurol. Autumn 2016; 10(4):80-85. Abstract We present a 7 year old boy afflicted with super-refractory seizure that responded poorly to antiepileptic drugs and sustained a long course of hospitalization and complications of high doses of medications as well as longstanding stay in hospital. The differential diagnoses were, fever-induced refractory epileptic encephalopathy (FIRES), and infectious and autoimmune encephalitis. However, work-ups had not revealed any evidence of any specific diagnosis, so we assumed that he was afflicted by viral infectious encephalitis as he had, fever, vomiting, and prodromal symptoms of infectious (most probably viral) disease prior to onset of the seizure attacks. References 1. William H. Theodore, Epilepsy and Viral Infections, Epilepsy Currents, Vol. 14, No. 1 Supplement 2014 pp. 35–42 2. Rima Nabbout, AnnamariaVezzani, Olivier Dulac, Catherine Chiron. Acute encephalopathy with inflammation-mediated status epilepticus. Lancet Neurol 2011; 10: 99–108. 3. Uri Kramer, Ching-Shiang Chi, Kuang-Lin Lin, Nicola Specchio, Mustafa Sahin, Heather Olson, Rima Nabbout, Gerhard Kluger, Jainn-Jim Lin, Andreas van Baalen. Febrile infection–related epilepsy syndrome (FIRES): Pathogenesis, treatment, and outcome, A multicenter study on 77 children. Epilepsia ; 201152(11):1956–1965. 4. Yael Hacohen, Sukhvir Wright, Patrick Waters, Shakti Agrawal, Lucinda Carr, Helen Cross et al. Paediatric autoimmune encephalopathies: clinical features, laboratory investigations and outcomes in patients with or without antibodies to known central nervous system autoantigens. J Neurol Neurosurg Psychiatry 2012;0:1–8. 5. Pedro J, Serrano-Castro, Pablo Quiroga-Subirana, Manuel Payan-Ortiz, Javier Fernandez-Perez. The expanding spectrum of febrile infection-related epilepsy syndrome (FIRES). Seizure 22 (2013), 153-155. 6. R Kneen BD, Michael E, Menson B, Mehta A, Easton C, Hemingway PE, Klapper A, Vincent M, Lim E, Carrol T. Solomon, On behalf of the National Encephalitis Guidelines Development and Stakeholder Groups. Management of suspected viral encephalitis in children e Association of British Neurologists and British Paediatric Allergy Immunology and Infection Group National Guidelines. J Infect 2012; 64, 449-477. 7. Raoul Sutter, Stephan Rüegg. Refractory Status Epilepticus: Epidemiology, Clinical Aspects and Management of a Persistent Epileptic Storm. Epileptologie 2012; 29: 186 – 193. 8. Simon Shorvon. Super-refractory status epilepticus: An approach to therapy in this difficult clinical situation. Epilepsia, 52(Suppl. 8):53–56, 2011. 9. Mustafa AM, Salih Heba Y, El Khashab Hamdy H, Hassan Amal Y. Kentab, Sara S. Al Subaei, Radwan M. Zeidan, Mohammed N. Al-Nasser, Saleh A. Othman. A Study on Herpes Simplex Encephalitis in 18 Children, Including 3 Relapses. Open Pediatr Med J 2009, 3, 48-57. 10. Thais Armangue, Josep O. Dalmau. Autoimmune Encephalitis. In: Robert M. Kliegman, Bonita F. Stanton, Joseph W. St. Geme III, Nina F. Schor, Richard E. Behrman, et al, editors. Nelson Textbook of Pediatrics, 20th Edition. Philadelphia, United States of America: Saunders; 2016: p. 2905-2910.